Från strategisk anpassning till institutionell allians - Mattias Lundin (Utbildning & Demokrati)
From Strategic Alignment to Institutional Alliance. A Study on LGBTQ Teachers’ Experiences of Belonging and Exclusion in Schools. The point of departure for this project is the importance of a sense of belonging to the contexts in which one is assigned to work, which in this case mainly refers to teachers’ sense of belonging to both their colleagues and their identity as lesbian, gay, bisexual, or transgender or queer (LGBTQ). By analysing seven narratives, the text aims to contribute knowledge on how LGBTQ teachers experience breaking the hetero norm by focusing on how belonging is created. Two situations in the data stand out with respect to how belonging is reconstructed for the teachers. These are characterised by institutional alliance building to create clarity about belonging and inclusion. The data raises the question of whether a success factor for creating belonging is schools’ efforts to develop their institutional support regarding inclusion and LGBTQ awareness.